PERTANGGUNG JAWABAN KORPORASI DALAM TINDAK PIDANA KORUPSI - Sugeng Jatmiko (The Juris, 2021)
The corporation as an institution that has a unique structure and is equipped with a set of provisions governing the actions of personnel in it, as a legal institution, an institution whose existence and capacity to do something is determined by law, often violates the law. In its development, it turns out that corporations are not only engaged in economic activities, but now their scope has begun to widen because they can cover the fields of education, health, research, government, social, culture, and religion. This study uses a normative juridical approach accompanied by empirical juridical, namely research that emphasizes the use of written legal norms related to the practices and perceptions of the informants. With the results of the research, namely that the criminal acts of corruption that can be carried out by corporations are corruption crimes as regulated in Article 2 paragraph (1), Article 3, Article 5 paragraph (1), Article 6 paragraph (1), Article 7, Article 13, Article 15, and Article 16 of Law No. 31 of 1999 in conjunction with Law No. 20 of 2001, and The existence of a corporation is not formed without a purpose and the achievement of the goal of the corporation, is always realized through natural human actions.